Fermented goat's milk modulates immune response during iron deficiency anemia recovery - García‐Burgos, María; Moreno‐Fernandez, Jorge; Díaz‐Castro, Javier; Alférez, María José; López‐Aliaga, Inmaculada (Journal of the science of food and agriculture, 2022)
BACKGROUND Iron deficiency and iron overload can affect the normal functioning of the innate and adaptive immune responses. Fermented milk products may enhance immune functions, but little is known about the effect of fermented milks on modulation of the immune response during iron deficiency anemia and recovery with normal or high dietary iron intake. Eighty male Wistar rats were randomly assigned to a control group fed a standard diet or to an anemic group fed a diet deficit in iron. Control and anemic groups were fed for 30 days with diets based on a fermented goat's or cow's milk product, with normal iron content or iron overload. RESULTS In general, during anemia recovery lectin and alternative complement pathway activity and lactoferrin decreased, because it improves iron homeostasis, which is critically important in immune system functions. Fermented goat's milk diet enhanced immune function during iron deficiency recovery, suppressed oxidant‐induced eotaxin and fractalkine expression due to the concurrent reduction of free radical production and pro‐inflammatory cytokines, and decreased monocyte chemoattractant protein‐1 and monocyte migration and adhesion. The increase in interferon‐γ can confer immunological colonization of gut microbiota and downregulate inflammation. CONCLUSION Fermented goat's milk consumption enhances immune function, modifying complement pathway activity and decreasing pro‐inflammatory cytokines as well as lactoferrin concentration, due to the improvement of iron homeostasis, which is critically important in the normal function of the immune system. © 2021 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.